Sosialisasi dan Edukasi Pelestarian Ekosistem Mangrove Berbasis Data Spasial Peta Tematik di Kelurahan Purirano Kota Kendari: Socialization and Education of Mangrove Ecosystem Conservation Based on Spatial Data of Thematic Maps in Purirano Sub-District, Kendari City - Widayati, Weka; Sawaludin, Sawaludin; Indriasary, Anita; Aulia, Weko Indira Romanti; Rahim, Saban (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Purirano Sub-district is one of the coastal areas of Kendari Bay that has a coastal boundary covered with mangrove forests. Mangrove forests on the coast of Purirano have a very important role in protection from disasters and can be utilized socio-economically. The purpose of this activity is to identify and map the mangrove ecosystem area and to conduct socialization and education on the preservation of the mangrove ecosystem in Purirano Sub-district, Kendari City. The method used in this activity is a survey and identification of the mangrove ecosystem area and map overlay as well as conducting socialization and education to school students, community, and government. There is a mangrove area of 39 hectares, consisting of 27 hectares of land owned by the community and 12 hectares of land owned by the government on the coast of Purirano Village. The mangrove ecosystem in Purirano Village has been damaged in several locations with a total area of 10.9 hectares. Socialization on mangrove conservation was conducted in the Quran Study Park, SMP 16 Kendari as well as the community and government of Puriraro Village regarding the importance of the mangrove ecosystem which has an ecological function as a coastal protector and a habitat for various marine biota, as well as having an economic and social function for the lives of the surrounding community. Through mangrove mapping, it is possible to plan the restoration of damaged mangrove conditions with rehabilitation and restoration activities involving the collaboration of all stakeholders in the Purirano Sub-district.